ANALISIS PENGARUH PEMBERIAN EDUKASI SDIDTK PADA IBU TERHADAP TUMBUH KEMBANG BALITA DI WILAYAH KERJA PUSKESMAS PINTU RIME KECAMATAN PINING KABUPATEN GAYO LUES PROVINSI ACEH TAHUN 2024 - Zuliarni Lubis; Elmina Tampubolon; Peny ariani (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2026)
SDIDTK is growth and development during the first 5 years of life. The aim of the research is for all toddlers aged 0-5 years and preschool children aged 5-6 years to grow and develop optimally. The writing aims to determine the effect of providing primary education to mothers on the growth and development of toddlers in the working area of ​​Pintu Rime Health Center, Pining District, Province. Aceh last year, the type of the research used quantitative with a quasi-experimental pre and post-test design, a population of 35 respondents in the Pintu Rime Community Health Center area, Pining District, Aceh Province, with consecutive technique, data sampling obtained from the results interviews by distributing questionnaires that have been prepared by researchers. The Data of analysis was carried out univariate and bivariate using the independent t-test with an alpha (a) value of 0.05. The results of research using the independent t-test obtained a significance value of 0.000, so it can be concluded that there was an influence of providing SDIDTK education to the mothers on the growth and development of toddlers in the Pintu Rime Health Center Working Area, Pining District, Aceh Province last year.